Intestinal colonization regulates systemic anti-commensal immune sensitivity and hyperreactivity - Burkhard, Regula; Koegler, Mia; Brown, Kirsty; Wilson, Kirsten; Mager, Lukas F.; Zucoloto, Amanda Z.; Thomson, Carolyn; Hebbandi Nanjundappa, Roopa; Skalosky, Isla; Ahmadi, Shokouh; McDonald, Braedon; Geuking, Markus B. (Frontiers in Immunology, 2023)
Healthy host-microbial mutualism with our intestinal microbiota relies to a large degree on compartmentalization and careful regulation of adaptive mucosal and systemic anti-microbial immune responses. However, commensal intestinal bacteria are never exclusively or permanently restricted to the intestinal lumen and regularly reach the systemic circulation. This results in various degrees of commensal bacteremia that needs to be appropriately dealt with by the systemic immune system. While most intestinal commensal bacteria, except for pathobionts or opportunistic pathogen, have evolved to be non-pathogenic, this does not mean that they are non-immunogenic. Mucosal immune adaptation is carefully controlled and regulated to avoid an inflammatory response, but the systemic immune system usually responds differently and more vigorously to systemic bacteremia. Here we show that germ-free mice have increased systemic immune sensitivity and display anti-commensal hyperreactivity in response to the addition of a single defined T helper cell epitope to the outer membrane porin C (OmpC) of a commensal Escherichia coli strain demonstrated by increased E. coli-specific T cell-dependent IgG responses following systemic priming. This increased systemic immune sensitivity was not observed in mice colonized with a defined microbiota at birth indicating that intestinal commensal colonization also regulates systemic, and not only mucosal, anti-commensal responses. The observed increased immunogenicity of the E. coli strain with the modified OmpC protein was not due to a loss of function and associated metabolic changes as a control E. coli strain without OmpC did not display increased immunogenicity.